Pre-malignant conditions diagnosed following a positive cancer signal from a multi-cancer early detection test - Choudhry, Omair A.; Kharge, Angana B.; Rego, Seema P.; Elias, Paul Z.; Buchanan, Adam H.; Lennon, Anne Marie; Papadopoulos, Nickolas; Diehl, Frank; Beer, Tomasz M. (Frontiers in Oncology, 2024)
Blood-based tests for multi-cancer early detection (MCED) are being developed to facilitate the detection of various cancer types. The Detecting cancers Earlier Through Elective mutation-based blood Collection and Testing study (DETECT-A) study evaluated an MCED test in 9,911 women, age 65-75, without personal history of cancer. In a post-hoc analysis, we report on the detection of precancerous neoplasms consequent to MCED testing and follow-up. Participants with positive baseline and confirmatory MCED testing underwent 2-deoxy-2[fluorine-18] fluoro-D-glucose positron emission tomography-computed tomography (PET-CT) and diagnostic evaluation as indicated by PET-CT results. We reviewed the electronic health records of participants with a precancerous neoplasm and summarized their clinical course. MCED results were positive in 134 participants. Clinically significant pre-malignant conditions were identified in three of these participants: A 71-year-old with an ovarian mucinous cystadenoma, a 67-year-old with an appendiceal mucinous neoplasm, and a 70-year-old with colon adenomas displaying high-grade dysplasia. All three participants underwent surgical treatment and remain alive and cancer-free as of last follow up. The diagnostic evaluation of a positive MCED test may occasionally reveal clinically significant pre-cancerous conditions amenable to interventions. The frequency of such findings and their clinical impact warrants further study.